The LIV-1-GRPEL1 axis adjusts cell fate during anti-mitotic agent-damaged mitosis - Chen, Pingbo (EBioMedicine, 2019)
BACKGROUND: Understanding how cells respond to mitotic poisons is of great biomedical and clinical significance. However, it remains unknown how cell-death or survival is determined during exposure to anti-mitotic drugs. METHODS: The biological effects of SLC39A6 (LIV-1) and GrpE-like 1 (GRPEL1) on mitotic exit and apoptosis were evaluated both in vitro and in vivo using flow cytometry, western blotting, xenografts and time-lapse imaging. The interactions between proteins and the ubiquitination of GRPEL1 were assessed by GST pull down, immunoprecipitation and mass spectrometry analysis. The expression of LIV-1 in cancers was assessed by immunohistochemistry. FINDINGS: Overexpression of LIV-1 led to direct apoptosis. Depleted for LIV-1 evade anti-mitotic agent-induced killing through a rapid exit from arrested mitosis. LIV-1 interacts with GRPEL1 and Stabilizes GRPEL1 Protein by Preventing Ubiquitylation of GRPEL1. LIV-1-GRPEL1 axis depletion works to reduce the mitotic arrest by inducing PP2A-B55α phosphates activity, while inhibit apoptosis by banding AIF and preventing the latter's release into the nucleus. Loss of function in this axis was frequent in multiple types of human epithelial cancer. INTERPRETATION: These data demonstrate that LIV-1-GRPEL1 axis dually regulates mitotic exit as well as apoptosis by interacting with PP2A B55α and AIF. Its discovery constitutes a conceptual advance for the decisive mechanism of cell fate during damaged mitosis. FUND: National Clinical Research Center for Obstetric and Gynecologic Diseases, the National Natural Science Foundation of China.